2006
DOI: 10.4219/jeg-2006-245
|View full text |Cite
|
Sign up to set email alerts
|

Gifted Today but Not Tomorrow? Longitudinal Changes in Ability and Achievement during Elementary School

Abstract: the term gifted implies a permanent superiority. However, the majority of children who score in the top few percentiles on ability and achievement tests in 1 grade do not retain their status for more than a year or 2. the tendency of those with high scores on one occasion to obtain somewhat lower scores on a later occasion is one example of regression to the mean. We first summarize some of the basic facts about regression to the mean. We then discuss major causes of regression: errors of measurement, individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 25 publications
0
60
0
5
Order By: Relevance
“…Indeed, one does not measure nonverbal ideation very well unless one measures spatial visualization abilities (Lohman, 1994(Lohman, , 2005. Spatially talented students are currently missed by modern talent search programs unless they happen to be mathematically or verbally gifted (recall that more than half of the top 1% in spatial ability are missed when talent searches rely on traditional math and verbal measures; Lohman & Korb, 2006;Shea et al, 2001 [see footnote 1]). This study demonstrates that an appreciable number of adolescents who might be identified by their extreme standing on spatial ability, if it were incorporated into talent search methods, would have interests in STEM pursuits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, one does not measure nonverbal ideation very well unless one measures spatial visualization abilities (Lohman, 1994(Lohman, , 2005. Spatially talented students are currently missed by modern talent search programs unless they happen to be mathematically or verbally gifted (recall that more than half of the top 1% in spatial ability are missed when talent searches rely on traditional math and verbal measures; Lohman & Korb, 2006;Shea et al, 2001 [see footnote 1]). This study demonstrates that an appreciable number of adolescents who might be identified by their extreme standing on spatial ability, if it were incorporated into talent search methods, would have interests in STEM pursuits.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence that the level and pattern of mathematical and verbal reasoning ability provide an incomplete picture of the intellectual talent among precocious youth when spatial ability is omitted. Calculations from normal curve theory reveal that, by selecting on the basis of scores of 500 on either the SAT-M or SAT-V before age 13, for example, talent searches miss more than half of the top 1% in spatial ability (Lohman & Korb, 2006;Shea et al, 2001). 1 This incomplete picture limits both the creation of optimal educational opportunities for them and the modeling of their subsequent development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Así por ejemplo Ramsden y colaboradores (2011) señalan como existen variaciones en las puntuaciones de niños y jóvenes que podrían relacionarse con cambios en la estructura cerebral debidos a diferentes factores tales como la edad, la estimulación, el sexo, etc…, o sea relacionables con la plasticidad cerebral. Sea este u otro el motivo, el caso es que se señalan cierto número de factores que intervienen en la variabilidad de las puntuaciones obtenidas a lo largo del tiempo por los tests más reputados, tales como el WISC (Lohman y Korb, 2006) o K-Bit -aunque este se haya mostrado como el test breve que mejor predice la sobredotación intelectual- (Mervis et al, 2012;Newton, McIntosh, Dixon, Willians y Youman, 2008) La cuestión de la estabilidad de puntuaciones tiene una importancia considerable pues precisamente en la estabilidad anales de psicología, 2014, vol. 30, nº 2 (mayo) temporal del C.I.…”
Section: Introductionunclassified
“…Ressalta-se que, como qualquer indivíduo, o superdotado não está imune a problemas. Os fatores genéticos e neurobiológicos influenciam o perfil cognitivo e intelectual das pessoas, mas a trajetória do desenvolvimento de um indivíduo pode mudar em uma direção favorável ou indesejável, recebendo influências diversas no decorrer das experiências de vida, bem como das oportunidades a ele oferecidas (Dai & Renzulli, 2008;Lohman & Korb, 2006;Moltzen, 2009;Pfeiffer, 2014;Sastre-Riba, 2013). …”
Section: Características Do Aluno Superdotadounclassified